О ВОЗМОЖНОСТИ СОЗДАНИЯ ПРОИЗВОДСТВА ТОВАРНОЙ БЕЛЕНОЙ ХИМИКО-ТЕРМОМЕХАНИЧЕСКОЙ МАССЫ В РЕСПУБЛИКЕ КАРЕЛИЯ - Шегельман, И.; Будник, П. (Северо-Кавказский научный центр высшей школы Федерального государственного образовательного учреждения высшего профессионального образования "Южный федеральный университет", 2015)
В статье рассмотрена проблема переработки лиственных пород деревьев. Приведены результаты анализа возможности создания производства товарной беленой химико-термомеханической массы в Республике Карелия как решение данной проблемы. Представлен краткий анализ рынка беленой химико-термомеханической массы в Российской Федерации. Analysis findings of possibility of establishing production of bleached chemi-thermomechanical pulp in the Republic of Karelia can be found in the article. The advantages of production of bleached chemi-thermomechanical pulp in comparison with paper pulp production are developed in the article. A brief analysis of Russian market of bleached chemi-thermomechanical pulp can be found in the article. Statement of reasons of establishing production of bleached chemi-thermomechanical pulp in the Republic of Karelia can be found in the article too. The establishing production of bleached chemi-thermomechanical pulp could help to solve a problem of deciduous trees processing which is in Republic of Karelia.